2019
DOI: 10.1093/jncics/pkz033
|View full text |Cite
|
Sign up to set email alerts
|

Deescalating Adjuvant Trastuzumab in HER2-Positive Early-Stage Breast Cancer: A Systemic Review and Meta-Analysis

Abstract: Background One year of adjuvant trastuzumab in combination with chemotherapy is the standard of care in early-stage human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Existing data on shortening trastuzumab treatment show conflicting results. Methods A search of PubMed and abstracts from key conferences identified randomized trials that compared abbreviated trastuzumab therapy to 1 year of treatment in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…This is especially advised for women >70 years of age and/or with comorbidities, that is, a high‐risk group for severe COVID‐19 disease if infected. Although Goldvaser's meta‐analysis [18] endorses 1 year of therapy, data from the PERSEPHONE study showed no worse patient outcomes with 6 months versus 12 months of adjuvant trastuzumab treatment in HER2‐positive early breast cancer [19]. Adjuvant anti‐HER2 therapy may be delayed for up to 2–3 months in patients receiving neoadjuvant chemotherapy in combination with anti‐HER2 antibodies. Adjuvant administration of trastuzumab‐DM1 (T‐DM1) is adequate for patients without pCR after neoadjuvant chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially advised for women >70 years of age and/or with comorbidities, that is, a high‐risk group for severe COVID‐19 disease if infected. Although Goldvaser's meta‐analysis [18] endorses 1 year of therapy, data from the PERSEPHONE study showed no worse patient outcomes with 6 months versus 12 months of adjuvant trastuzumab treatment in HER2‐positive early breast cancer [19]. Adjuvant anti‐HER2 therapy may be delayed for up to 2–3 months in patients receiving neoadjuvant chemotherapy in combination with anti‐HER2 antibodies. Adjuvant administration of trastuzumab‐DM1 (T‐DM1) is adequate for patients without pCR after neoadjuvant chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Several articles [8,[17][18][19][20][21][22] investigating shorter treatment durations for trastuzumab have been published subsequent to this initial review.…”
Section: Rationale For Eml Future Reviewmentioning
confidence: 99%
“…Six meta-analyses [17][18][19][20][21][22] were consi dered for this review; however, none met the inclusion requirements. They were either of low quality in terms of methodological rigour and/or failed to include the results from key clinical trials.…”
Section: New Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ensure breast cancer continued care and treatment and protect patients and healthcare professionals from the COVID-19 pandemic, a priority program has been developed to minimize patient hospitalization and ensure optimal patient care. In this perspective, instead of the proposed general deferral strategy [63], it was decided not to defer breast cancer treatment that have been classi ed as at medium/high priority by ESMO [64], while avoiding or delaying low priority interventions only. Patients and staff safety have been demanded to the general (strict) protection policy of the hospital.…”
Section: Guidelines/recommendation For Breast Cancermentioning
confidence: 99%